2012
DOI: 10.1186/1447-056x-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Reporting new cases of anaemia in primary care settings in Crete, Greece: a rural practice study

Abstract: BackgroundEarly diagnosis of anaemia represents an important task within primary care settings. This study reports on the frequency of new cases of anaemia among patients attending rural primary care settings in Crete (Greece) and to offer an estimate of iron deficiency anaemia (IDA) frequency in this study group.MethodsAll patients attending the rural primary health care units of twelve general practitioners (GPs) on the island of Crete for ten consecutive working days were eligible to participate in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Despite the within-gender variations, these major chronic conditions appear to be more frequent in the population of our study compared with other Greek studies. 27 , 31 , 32 Nevertheless, our findings seem to be in accordance with the literature, which suggests that patients suffering from heart diseases, COPD, or type 2 diabetes are at a higher risk for CAP. 19 , 33 , 34 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the within-gender variations, these major chronic conditions appear to be more frequent in the population of our study compared with other Greek studies. 27 , 31 , 32 Nevertheless, our findings seem to be in accordance with the literature, which suggests that patients suffering from heart diseases, COPD, or type 2 diabetes are at a higher risk for CAP. 19 , 33 , 34 …”
Section: Discussionsupporting
confidence: 91%
“…This finding was expected, as a recent primary care study regarding new cases of anaemia that was conducted in a similar setting in rural Crete found that 77% of participants were overweight or obese as well. 27 …”
Section: Discussionmentioning
confidence: 99%
“…The mean Hb levels in the group with confirmed anaemia, as identified by the portable analyzer, were 11.1 g/dl, whereas the mean Hb levels acquired by the whole blood count were 11.4 g/dl. Sixteen of the 45 patients with anaemia (35.6%) had IDA, meaning their ferritin levels were less than 30 ng/ml [18].…”
Section: Research Datamentioning
confidence: 99%
“…Moreover, there are primary care PBRNs that have been set up in some other European countries (26)(27)(28)(29)(30). There are some positive examples of practice-based research networks in rural areas of selected European countries (31)(32)(33)(34). These enable the study of primary care problems as well as the process of continuing quality improvement within primary care settings (29).…”
Section: Practice-based Research Network In Family Medicinementioning
confidence: 99%
“…The network is very active and has produced many research results (31)(32)(33)49). In many European countries, research in rural family medicine is quickly developing.…”
Section: Practice-based Research Network In Rural Family Medicinementioning
confidence: 99%